Amateur Gold Farming in China: “Chinese Ingenuity,” Independence, and Critique - Liboriussen, Bjarke (Games and Culture, 2016)
Informed by a mix of theoretical sources and interviews with middle-class Chinese amateur gold farmers, this article argues that within China, the figure of the Chinese gold farmer might function as focus for reflection on Chineseness and China’s role in an increasingly interconnected world, rather than as a carrier of third-world stereotype as it tends to do in the West. The concept of shanzhai—often associated with sometimes comical, sometimes innovative Chinese copying of foreign consumer goods—is employed as a key analytical tool and helps highlight the themes of “Chinese ingenuity,” independence (from game operators and to some extent also parents), and critique (of games).
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); _Nettoyé